An empirical reappraisal of the four types of cyclists. (July 2020) - Cabral, Laura; Kim, Amy M.
Highlights: The Four Types of Cyclists typology generates heterogeneous comfort patterns. Our data-driven segmentation yields more homogeneous comfort patterns. Cyclists form three categories, not four, based on comfort, intent, frequency. Types: Uncomfortable or Uninterested, Cautious Majority, Very Comfortable Cyclists. Abstract: The Four Types of Cyclists is a widely adopted typology developed by Portland's Bicycle Coordinator, Roger Geller. No Way No How, Interested but Concerned, Enthused and Confident, and Strong and Fearless have become ubiquitous in academic literature and practice. However, the classification was subjectively developed and contains several known contradictions. This research aims to develop a data-driven typology using near-identical explanatory variables to those of the Four Types of Cyclists. The objective is to develop a typology with a similar functional purpose, but derived using statistical methods. An online survey was distributed to a panel of Edmonton, Canada, residents to this effect, and the use of video clips rather than descriptions is tested as a means to assess comfort on different types of cycling infrastructure. Cluster Correspondence Analysis is used to carry out the segmentations, including variables of comfort, cycling intent, and cycling in the previous summer. The survey sample tends to segment into three categories, as opposed to the four suggested by Geller: Uncomfortable or Uninterested, Cautious Majority, and Very Comfortable Cyclists. The Four Types of Cyclists typology is also shown to generate heterogeneous comfort patterns within each cyclist type, a limitation our empirically-derived segmentations overcome.